Combination treatment of extensive and recalcitrant alopecia areata with oral and topical steroids with topical minoxidil: An open-label study of efficacy and safety in pediatric patients - Vivek Kumar Dey (Wolters Kluwer Medknow Publications, 2016)
Background: Alopecia areata (AA) is an autoimmune disorder characterized by nonscarring alopecia affecting scalp and body hair. Treatment of AA in pediatric age group is challenging because of unpredictable course, uncertain natural history, potential side effects of medicines, and psychological morbidity. Moreover, no clear guidelines for treatment of pediatric AA are available. Objective: The objective of this study is to assess efficacy and safety of a combination treatment of extensive and recalcitrant AA with oral and topical steroids with topical minoxidil. Materials and Methods: Sixteen children (nine girls and seven boys) aged 6-15 years with severe and recalcitrant AA were included in this study. All were prescribed the regimen of combination of oral and topical steroid with topical minoxidil 2% solution. Oral steroid was tapered over 12 weeks, and topical steroid was withdrawn at the end of 24 weeks. Patients were maintained on topical minoxidil for next 9-12 months and closely followed up. Results: The average age of participants was 10.81 years, and the duration of disease was ranged from 3 months to 30 months. Response to our regimen was good in cases of extensive AA and ophiasis, compared to alopecia totalis. The participant having alopecia universalis did not respond at all to the regimen. Participants tolerated the regimen well with mild and easy to manage side effects and only few relapses. Conclusion: Finding an effective and safe treatment regimen for AA, especially in children is difficult. Our regimen allows for more rapid lowering of oral doses with maintaining the cosmetic response and minimizing the side effects. Therefore, a trial course of this regiment would seem to be a reasonable approach for nearly hopeless but highly motivated pediatric patients of extensive and recalcitrant AA.